2003
DOI: 10.1097/00000658-200301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses and Prediction of Major Infection in Patients Undergoing Transhiatal or Transthoracic Esophagectomy for Cancer

Abstract: ObjectiveTo investigate alterations in immune responses after transhiatal versus transthoracic esophageal resection and to evaluate the role of preoperative immune functions in predicting postoperative infectious complications. Summary Background DataImpaired immune defense is associated with a decreased resistance to infection. Patients undergoing esophageal resection via a transhiatal or transthoracic approach are prone to develop infectious complications. There are no randomized data on immune responses aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 33 publications
4
39
1
Order By: Relevance
“…Peritonitis patients may develop immunosuppression as a result of initially upregulated responses during intra-abdominal infection combined with the effects of surgery. Surgery itself can suppress the immune response (42), as was confirmed in experimental studies reported previously (1,37). Conditional immunosuppression plus low functional MBL levels may reduce the inhibition of yeast proliferation.…”
Section: Discussionsupporting
confidence: 61%
“…Peritonitis patients may develop immunosuppression as a result of initially upregulated responses during intra-abdominal infection combined with the effects of surgery. Surgery itself can suppress the immune response (42), as was confirmed in experimental studies reported previously (1,37). Conditional immunosuppression plus low functional MBL levels may reduce the inhibition of yeast proliferation.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies demonstrated that T helper cells decreased and T suppressor cells increased significantly as early as 1 day after surgery [22][23][24] . Many subsequent studies also confirmed that surgery for patients with lung cancer [25] , esophageal cancer [26] , gastric cancer [27,28] and colorectal cancer [29,30] induced immediate severe immunosuppression. For cancer patients, an important function adversely affected by this immunosuppression is the anti-tumor response itself.…”
Section: Discussionmentioning
confidence: 85%
“…Trans-Hiatal and Transthoracic techniques cause severe interruptions of monocytes and reduction of cytokine production by Tlymphocyte. Surgical procedures in esophageal cancer patients reduce the level of safety in the immune system (45).…”
Section: Discussionmentioning
confidence: 99%